Species-Dependent Chelation of 241Am by DTPA Di-Ethyl Ester. Issue 4 (April 2015) - Huckle, James E.; Sadgrove, Matthew P.; Mumper, Russell J.; Jay, Michael
Abstract : Abstract: Diethylenetriaminepentaacetic acid (DTPA) is an FDA-approved chelating agent for enhancing the elimination of transuranic elements such as americium from the body. Early access to therapy minimizes deposition of these radionuclides in tissues such as the bone. Due to its poor oral bioavailability, DTPA is administered as an IV injection, delaying access. Therefore, a diethyl-ester analog of DTPA, named C2E2, was synthesized as a means to increase oral absorption. As a hexadentate ligand, it was hypothesized that C2E2 was capable of binding americium directly. Therefore, the protonation constants and americium stability constant for C2E2 were determined by potentiometric titration and a solvent extraction method, respectively. C2E2 was shown to bind americium with a log K of 19.6. The concentrations of C2E2, its metabolite C2E1, and DTPA required to achieve effective binding in rat, beagle, and human plasma were studied in vitro. Dose response curves for each ligand were established, and the 50% maximal effective concentrations were determined for each species. As expected, higher concentrations of C2E2 were required to achieve the same degree of binding as DTPA. The results indicated that chelation in beagle plasma is more representative of the human response than rats. Finally, the pharmacokinetics of C2E2 were investigated in beagles, and the data was fit to a two-compartment model with elimination from the central compartment, along with first-order absorption. Based on the in vitro data, a 100 mg kg −1 dose of C2E2 can be expected to have an effective duration of action of 3.8 h in beagles.